The software and hardware architecture of the real-time protection of in-vessel components in JET-ILW. (29th May 2019) - Huber, V.; Huber, A.; Kinna, D.; Matthews, G.F.; Sergienko, G.; Balboa, I.; Brezinsek, S.; Lomas, P.J.; Mailloux, J.; McCullen, P.; Mertens, Ph.; Rimini, F.G.; et al.
Abstract: For the first time, the JET operation in deuterium–tritium (D–T) plasma, which is scheduled to take place on JET in 2020, will be performed in the ITER mix of plasma-facing component materials. In view of the preparation of the DT campaign (DTE2), several aspects of the plasma operation require significant improvements, such as a real-time protection of the first wall. The risk of damaging the metallic PFCs caused by beryllium melting or cracking of tungsten owing to thermal fatigue required a new reliable D–T compatible active protection system. Therefore, the future development of the JET real time first wall protection is focused on the D–T campaign and the ITER relevant conditions which may cause failure of camera electronics within the Torus hall. In addition to the technological aspect, the intensive preparation of the diverse software tools and real time algorithms for hot spot detection as well as alarm handling strategy required for the wall protection is in progress. This contribution describes the improved design, implementation, and operation of the near infrared (NIR) imaging diagnostic system of the JET-ILW plasma experiment and its integration into the existing JET protection architecture. To provide the reliable wall protection during the DTE2, two more sensitive logarithmic NIR camera systems equipped with new optical relays to take images and cameras outside of the biological shield have been installed on JET-ILW and calibrated with an in-vessel calibration light source (ICLS). Additionally, post-pulse data visualization and advanced analysis of all types of imaging data is provided by the new software framework JUVIL (JET users video imaging library). The formation of hot spots is recognized as a significant threat due to rapid surface temperature rise. Because it could trigger the protection system to stop a pulse, it is important to identify the mechanisms and conditions responsible for the formation of such hot spots. To address this issue the new software tool 'Hotspot Editor' has been developed.